Inovasi Pembelajaran Sejarah - Ilham Pramayogi; Rully Putri Nirmala P; Wiwin Hartanto (LP4MK STKIP PGRI Lubuklinggau, 2019)
This research aims to analyze the form of innovation in historical learning at the secondary education level. This is in the background because of the decreasing interest of students in learning history subjects. The method used in this study is a qualitative research method that is a type of document study so that this study in other words is not done directly, but this research was conducted by looking for relevant sources in accordance with the current study. The results of this study are (1) we can find out whether what is actually the background of students to be reluctant to learn history, (2) we can find suitable learning models in order to encourage students to be interested in learning history, (3) we can know that from historical learning there will be a great contribution to foster a sense of nationalism for students as the next generation.